Identification of Bacteria Associated with Antimicrobial Sponges on Nangka Besar Island, Central Bangka - Siti Ade Nur Milah (Biology Study Program, Faculty of Science and Engineering, University of Bangka Belitung, Indonesia, 2025)
Sponges are benthic biota that are found in all marine and freshwater ecosystems. This animal has many pores and channels in all parts of its body. Marine organisms such as sponges often live in association with marine fungi that can produce antimicrobial compounds. This study aims to determine the types of sponges and the types of bacteria found in the waters of Nangka Island, Central Bangka Regency. The samples obtained were then incubated for further purification of the bacterial isolates. The results of this study indicate that there are 4 types of sponges, namely Haliclona mediterranea, Gelliodes fibulata, Cribrochalina sp, and Spongilla lacustris. Identification of the bacteria itself can be done by means of an antibacterial test using a disc test by 3 kinds of bacteria, namely Pseudomonas sp. Escherichia coli, Staphylococcus aereus and the results of antibacterial tests using extracts from 4 species against 3 types of test bacteria showed that only one type of bacteria had a response to the test material. Keywords: Antimicrobial, Bacteria, Sponge, Pseudomonas sp. Escherichia coli, Staphylococcus aureus